WALANT Decreases Costs of Surgery to Increase Access and Help Alleviate Poverty in East Africa - Pankaj Jani, MMed, FRCPS, FCS(ECSA); James Kariuki, MBChB; Nilkanth V. Jani, MBChB; Sameer M. Pandya, MD; Ankit J. Dave, MBChB, MMed(Orth), Dip SICOT; Sara M. Amin, MRCSed, MD, SMSB; Baiya A. Rashid, BSc, MD, MMED; Donald H. Lalonde, MD, FRCSC (Plastic and Reconstructive Surgery, Global Open)
Summary:. Surgery is essential to help people regain health and get back to work. Many Africans cannot afford traditional surgery because the sedation and main operating room sterility components are much too expensive. This often results in crushing debt for African families. Lack of access to surgery leads to poverty and poverty leads to lack of access to surgery. Wide-awake local anesthesia no tourniquet surgery, minimal pain tumescent local anesthesia, and evidence-based sterility are 3 disruptive game-changing innovations that eliminate the expensive general anesthesia and/or main operating room sterility components for many operations. Eliminating the tourniquet removes its need for sedation. Minimal pain tumescent local anesthesia enables comfortable numbing of large areas of the body to perform sedation-free operations such as soft tissue facial reconstruction, long bone fracture fixation, breast surgery, hernia repair, extremity surgery, and skin grafting. Evidence-based sterility has proven that many operations can be performed with field sterility outside of the main operating room environment with no significant increase in infection rates. No sedation also means no need for the main operating room environment. Moving some surgery out of the main operating room increases access for other operations that need full sterility to be accomplished. Since January 2020, these 3 disruptive changes have been adopted in 75 hospitals in 8 East African countries. This article documents how these changes have decreased the costs of surgery for the patients and, therefore, increased access to surgery, which helps alleviate poverty.